Improved estimation of glomerular filtration rate (GFR) by comparison of eGFR(cystatin C) and eGFR(creatinine) - Grubb, Anders (Informa Healthcare, 2012)
OBJECTIVE: GFR-prediction equations based upon cystatin C and creatinine have better diagnostic performance in estimating GFR than equations based upon only one of the two markers. The present work concerns in what way a comparison between separate estimations of GFR based upon cystatin C (eGFR(cystatin C)) or creatinine (eGFR(creatinine)) can be used to evaluate the diagnostic performance of a combined cystatin C- and creatinine-based estimation of GFR. METHODS: The difference between eGFR(cystatin C) and eGFR(creatinine) was compared with measured GFR (iohexol clearance) and a combined cystatin C- and creatinine-based estimation of GFR in a Swedish-Caucasian cohort of 857 adult patients. RESULTS: A difference between eGFR (cystatin C) and eGFR(creatinine) of ≥ 40% indicated a markedly reduced diagnostic performance of the combined cystatin C- and creatinine-based estimation of GFR. CONCLUSION: Comparison of the agreement between eGFR(cystatin C) and eGFR(creatinine) can be used to evaluate the diagnostic performance of combined cystatin C- and creatinine-based estimations of GFR. If ‘threshold values’ for discordance are exceeded, it must be considered whether the clinical context requires the use of an invasive gold standard method to measure GFR. In some clinical contexts either creatinine or cystatin C are known to be invalidated as markers of GFR and in these situations the use of only the cystatin C- or the creatinine-based GFR estimate should be considered when the ‘threshold values’ are exceeded.